Antibody response to Babesia bigemina and Babesia bovis by vaccinated and unvaccinated cattle in an endemic area of South Africa - Penzhorn, Barend Louis (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2001.